2019
DOI: 10.30525/2256-0742/2019-5-4-248-262
|View full text |Cite
|
Sign up to set email alerts
|

Market Efficiency, Financial Integration, and Shock Transmission (Empirical Evidence From D-8 Economies)

Abstract: The specific purpose of the Developing-8 economies is to integrate the endeavours of each member countries to excel economic cooperation and facilitation among the Islamic countries to enhance the investment opportunities and not to put pressure on the geopolitical environment of the world. The purpose of this study is to visualize the market efficiency, financial integration, and shock transmission process in the D-8 Economies for the period from Jan 2011 to Dec 2016. Daily market data is taken for KSE, DSE, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The research suggested that economic integration and cooperation among economies could enhance growth opportunities in trade and corporate investments, including in the retail sector. This study highlights the economic implications of technological advancements and market dynamics for retail businesses (Khurram et al, 2019).…”
Section: Economic Implications Of Mixed Reality In Retailmentioning
confidence: 90%
See 1 more Smart Citation
“…The research suggested that economic integration and cooperation among economies could enhance growth opportunities in trade and corporate investments, including in the retail sector. This study highlights the economic implications of technological advancements and market dynamics for retail businesses (Khurram et al, 2019).…”
Section: Economic Implications Of Mixed Reality In Retailmentioning
confidence: 90%
“…The research highlights the need for retail businesses to adapt to changing market conditions and consumer preferences, particularly in the context of digital transformation (Chernyak & Yakymchuk, 2021). Khurram et al (2019) explored market efficiency, financial integration, and shock transmission in D-8 economies, providing insights into the economic dynamics relevant to the retail sector. The study used various econometric tests to analyze market data and assess the efficiency of equity markets.…”
Section: Economic Implications Of Mixed Reality In Retailmentioning
confidence: 99%
“…The study concluded that 􀅫inancial market's innovation signi􀅫icantly exposed cost, and distress regarding 􀅫inancial streams. Khuram, Hamid, and Akash (2019) documented research to explore transmission disparities, integration regarding to hit 􀅫inancial and market ef􀅫iciency. The data of D-8 developing economies were taken from 2011 to 2016 and applied Unit root test, co integration, granger causality, VECM and impulse response tests.…”
Section: Introductionmentioning
confidence: 99%